Pemberdayaan Ekonomi Keluarga melalui Pelatihan Pembuatan dan Pemasaran Minuman Sehat dan Menyegarkan dengan Brand "Balirik" - Rika Neldawaty; Suherman Suherman; Vina Neldi; Abd Halim (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
The community service partner faced persistent challenges, including limited household income and inadequate entrepreneurial skills to capitalize on post-pandemic culinary business opportunities. This community empowerment program aimed to strengthen family economic resilience by diversifying healthy beverage products made from locally sourced ingredients under the "BALIRIK" brand. The program sought to enhance the partner's production capacity, business management, and marketing competencies to create sustainable income-generating opportunities. The implementation consisted of three stages: (1) production training covering recipe standardization, food processing techniques, and hygiene practices; (2) business management training focusing on calculating the Cost of Goods Sold (COGS), pricing strategies, and simple bookkeeping; and (3) digital marketing training emphasizing product branding, visual identity development, and social media optimization. The results demonstrated an 85% improvement in the partner's knowledge and skills regarding hygienic beverage production and business management. In addition, the program successfully established the "BALIRIK" brand identity, making the product more competitive in the local market. To ensure program sustainability, intensive post-training mentoring was provided to monitor production consistency, strengthen digital marketing implementation, maintain product quality, and support continuous sales growth and long-term business development.